De Garengeot hernia in an elderly female: a case report - Guidi, Gonçalo; Fernandes, Urânia; Martins, Daniela; Lage, José C.; Taveira, Francisco; Próspero-Luis, Fernando; Pinto-de-Sousa, João (International Surgery Journal, 2023)
A groin hernia is known as De Garengeot hernia when the appendix is located within the sac of a femoral hernia, with or without associated acute appendicitis. The true incidence of de Garengeot’s hernia is difficult to assess due to its rarity. Most of the times, De Garengeot hernia are presented acutely when incarcerated which turn them indistinguishable from other incarcerated femoral hernias at clinical examination. Treatment of De Garengeot hernia is an emergency, as it is for any femoral hernia incarcerated. After initial resuscitation, surgical treatment is mandatory without further delay. The surgical approach and the options to consider are dependent on the presence of incarceration and of septic environment at the time of diagnosis.